Survival Genius Analysis Faced by the Main Characters in All Is Lost Movie by Jeffry Mcdonnell Chandor - Kaa, Dewi Yanti Bangi; Utami, Ni Made Verayanti (Austronesian: Journal of Language Science & Literature, 2025)
This study investigates the psychological dimensions of human behavior as depicted in the film All Is Lost, directed by J.C. Chandor. Focusing on the main character, the research aims to examine behavioral patterns and uncover underlying psychological aspects presented throughout the narrative. The analysis is based on Sigmund Freud’s Semium (2006) theory of defense mechanisms and personality structure, as well as Anna Freud’s (1936) elaboration on defense mechanisms. Employing a descriptive qualitative method, data were collected through careful observation of scenes and note-taking techniques. The findings reveal four distinct psychological aspects portrayed by the protagonist, with the survival instinct emerging as the most dominant. This study highlights how cinematic representation can reflect complex psychological processes in extreme conditions.